Mechanoplasmonics in clusters of metal nanoparticles: theory and modeling - Serebrennikov, Аleksey Мikhailovich (Computational Continuum Mechanics, 2013)
In this work, the theoretical model explaining frequency scaling and multi photon effects in metal nanoparticles has been suggested. Its capabilities are demonstrated in relation to the second and third harmonic generation phenomena and the four-wave mixing phenomena as well. The continuum mechanical description of the electron gas of valence electrons underlies the theory. The principal equations of motion are deduced from Hamilton’s principle of least action. The compatibility of the model with the Drude theory is demonstrated in the linear case. On the basis of the proposed model we investigate the effect of Coulomb interaction in clusters of metal nanoparticles and the resulting motion of particles under the assumption of the compliance of an ambient medium.
Keywords: nonlinear plasmonics; metal nanoparticles; second harmonic generation; four-wave mixing